Occurrence distribution and abundance of plant parasitic nematodes of bananas in Uganda - Kashaija, I.; Speijer, P.; Gold, C.; Gowen, S. (1994)
A survey of plant parasitic nematodes in the major banana growing areas of Uganda was conducted in 1993. A total of 120 root samples were collected from 24 sites. Eight nematode species belonging to four genera were encountered. The most widespread species were Pratylenchus goodeyi (cob) sher and Allen, and Helicotylenchus multicinctus (cob) Golden, occurring in 96% and 83% of the site, respectively. Radopholus similis (cobb) Thorne and Meloidogyne spp. Were also prevalent although their distribution was dependent on elevation. P. coffeae (Zimmerman) Goodey, P. zeae (Graham), H. pseudorobustus and H. dihystera (colbran) which were previously not reported on bananas in Uganda, were also found in a few sites.